Implementasi E-Learning dalam Pembelajaran PAI pada Masa Covid 19 di SMA Negeri 4 Pariaman - Moni Anzika; Alfurqan Alfurqan (ISLAMIKA, 2022)
The COVID-19 pandemic has hit the whole world and Indonesia is not spared. One of the impacts of the COVID-19 pandemic is the disruption of the learning process in all elements of education. E-learning is one alternative in overcoming this condition. The research aimed to see: the application of E-learning in Islamic Religious Education learning at SMAN 4 Pariaman and the weaknesses and strengths in the implementation of E-learning in Islamic Religious Education learning. The method used in this research is qualitative research with a descriptive approach. The research was conducted at SMA Negeri 4 Pariaman. Data was collected using the methods of interview, observation, and documentation. The results showed that: first, the implementation of E-learning in Islamic Religious Education learning at SMAN 4 Pariaman went well even though there were several obstacles. The obstacles found were internet connection problems, and students' willingness to learn. Second, the advantages in implementing E-learning in Islamic religious education are the ease of access to materials, the ease of designing materials, and the ease of delivering more detailed material and for the drawbacks, not all have mobile phones and not all students' homes are covered by internet access services.